The Influence of Using Learning Media Based on Technological Knowledge on Students' Science Literacy Skills in the Excretory System Material - Nurhayati, Siti; Masitah; Akhmad; Jailani; Serena, Nelda Anasthasia (PendIPA Journal of Science Education, 2025)
This study aimed to determine the effect of the use of Technological Knowledge-based learning media on students' scientific literacy skills on the excretion system material in class XI biology subjects at SMA Negeri 5 Samarinda. The type of research used was experimental research with quantitative methods in the form of a quasi-experimental design type of the pretest-posttest control group design. The results of students' scientific literacy skills obtained the results of the N-Gain test, which is 0.59 with a moderate category, and the results of the t-test with a significance value of 0.000 <0.05. Based on these results, it was found that the use of Technological Knowledge-based learning media has a significant effect on students' scientific literacy skills on the excretion system material in class XI of SMA Negeri 5 Samarinda.